MITIGATING OPERATIONAL AND CREDIT RISK: INTERNAL AUDIT AS A DECISION-MAKING TOOL IN NBFCS AND HFCS IN VIDARBHA - Gupta, Satish Kumar Hiralal; Joshi, Parag Madhukar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In order to reduce operational and credit risks in NBFCs and HFCs in the Vidarbha area, this research looks at the function of internal audits as a strategic choice-making tool. The study emphasises how internal audit departments improve risk management, efficiency in operations, and regulatory compliance by using a descriptive research approach and data gathered from 100 professionals using structured questionnaires. Results show that internal audit procedures significantly improve the number of loan defaults and operational errors, highlighting their significance for long-term financial control. To improve institutional resilience, the report suggests implementing risk-based internal inspection frameworks and fostering more cooperation between the audit, risk, and regulatory departments.